2018
DOI: 10.1016/j.ptsp.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a four week jump-training program on frontal plane projection angle in female gymnasts

Abstract: The jump training program was successful in improving FPPA in female gymnasts and is advised to be implemented into the warm-ups and training programs of competitive female gymnasts to improve FPPA and therefore reduce the risk factors associated with knee injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Their results showed that plyometric training reduces knee abduction and hip adduction. Colclough et al examined the effects of a 4-week jump training on frontal-plane projection angle in female gymnasts during single-leg landing [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that plyometric training reduces knee abduction and hip adduction. Colclough et al examined the effects of a 4-week jump training on frontal-plane projection angle in female gymnasts during single-leg landing [31].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that plyometric training programs by focusing on the knee alignment and improving the landing techniques during dynamic activities, reduce the angle of knee valgus and the ground reaction forces [10,11]. On the other hand, this training improves feedback and feedforward activities simultaneous with matching mus-…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding these limitations, this study has important strengths. Despite the high injury rates in young artistic gymnastics [51] and the risk reducing benefits of strength and conditioning for young female athletes [33,52], there is a dearth of published literature examining individual training responsiveness of this population to neuromuscular training. This exploratory study offers a novel contribution to the literature by providing researchers and practitioners with insight into the differentiated responsiveness of young female gymnasts to a neuromuscular- and gymnastics-training stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Further, three of the four artistic disciplines that female gymnasts compete in (vault, beam and floor exercise) are heavily reliant on explosive lower-limb rebounding and jumping activities, which all utilize various expressions of the stretch-shortening cycle (SSC) [36]. Consequently, rebounding and jumping performance of artistic gymnasts are commonly assessed to identify key determinants of the sport [8,29,31,50], determine physical profiles [46,53] and evaluate the efficacy of training interventions [7,11,28,37].…”
Section: Introductionmentioning
confidence: 99%